Can Teachers Be Game Designers? - Sylvester, Arnab; Minoi, Jacey Lynn; Fitri Suraya, Mohamad; Morini, Luca; Clarke, Samantha (Academic Conferences and Publishing International Limited, 2019)
Games, which are more readily blended with existing educational techniques and practices, are more likely to be accepted by teachers as useful resources. Hence, it is worth ensuring the design of game-based learning resources might support such blending, which can range from pragmatic considerations, such as how well an intended play session fits within a teaching schedule or homework arrangement, to pedagogical designs, which seek to address shortcomings in didactic instruction. To promote the sense of ownership and autonomy to break the barriers of adoption, not only that teachers should be part of the development process but they should also be empowered to create or co-create their games - removing the barriers to the development of game-based learning resources. In the CreativeCulture initiative, a project funded by the Newton Fund, teachers are empowered to create their games towards engaging learners with educational contents. Game making can be used to foster the development of transversal skills, such as 21st-century skills, where individuals can design and construct their games, often working in teams, allowing them to engage in a task that involves, and at the same time, fosters collaboration, problem solving and creativity. This case study extends the game design thinking process in proposing a solution for teachers in co-creating and developing their educational games. This process is examined through a study involving 43 teachers over two academic semesters. A total of eighteen game-based learning resources have been developed through the initiative, which has been tested in seven local primary schools in rural and semi-rural areas in Malaysia. This paper reflects on the lessons learnt and observations, which may provide insights on how game-based learning can remove barriers to the process of innovating the way we teach and learn.